Co-Operation, Compliance, Perseverance: The Finnish Model for Clinical Drug Research - Itkonen, Paivi; Valtonen, Paivi; Koskinen, Hannele; Aittasalo, Harri (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
In spite of the after-effects of the global economic depression in the past few years, the direction of drug research in Finland is clear and positive. The industry is growing at a pace greater than the economic indices. Nordic collaboration has a significant influence on drug research and development in Finland. Recent statistics by the Finnish Medicines Agency (FIMEA), which supervises drug research and development indicates that the number of new clinical trials initiated last year remained consistent as the year before, approximately 122 commercial (sponsored) trial notifications and 30 noncommercial (non-industry sponsored) trials were recorded in 2013. Finland has a long tradition for vaccine trials in Finland and recently a significant thrust in oncology research, especially the development of targeted receptor-level drugs. Finland is a particularly suitable country for clinical drug research given the professional expertise of researchers, physicians and other health care personnel, irrespective of specialty. In addition, it is an equal opportunity for society whereby health care services are statutorily available to everyone.
Keywords: Clinical research